AWS Certified Database – Specialty (DBS-C01) Cert Prep: 4 Monitoring and Troubleshooting. - Carpenter, Tom (linkedin.com, 2020)
Prepare to take and pass the AWS Certified Database – Specialty (DBS-C01) exam as you review strategies for monitoring and troubleshooting AWS database solutions.